Determinación de los niveles de metales pesados en la microcuenca del río Carrizal del cantón Bolívar, provincia de Manabí - Andrade Chunga, Ena Monserrate (2016)
The objective of this thesis was to identify the concentration of heavy metals (cadmium, lead and mercury) in the Carrizal River micro-watershed in Bolivar, province of Manabí, with the aim of assessing the existing water pollution in the area. We established six sampling sites located in the Severino, Balsa en Medio, Tigre Adentro, Río Chico, Puente río Carrizal and Aguacate villages. At each geo-referenced location, we took three water samples during October, November and December 2015. This research was quantitative and non-experimental, and analyses were conducted and the laboratories of INP (Instituto Nacional de Pesca/National Fisheries Institute) and IIRN (Instituto de Investigacion de Recursos Naturales de la Universidad de Guayaquil/University of Guayaquil Natural Resource Research Institute). In conclusion, results showed concentrations below zero for the metals analyzed. Which means that, according to the Ecuadorian environmental legislation standards (Ministerial Agreement Number 028), the water in the Carrizal micro-watershed has no content of heavy metals, and all the values are within maximum permissible limits.